Analisi Analisis faktor yang berhubungan Dengan kejadian hipertensi pada wanita monopause di puskesmas sihapas barumun tahun 2024 - Rizki, Elda Naila; SKM, M.kes, Dr. Elmina Tampubolon; Sst,M.keb, Bd. Peny ariani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2024)
The disease that causes death in the world is hypertension. Especially in developing countries, every year it increases. Hypertension cases in menopausal women are higher than men, this is due to a decrease in estrogen levels. This study aims to analyze factors associated with the incidence of hypertension in menopausal women at the Sihapas Barumun Community Health Center in 2023. This research is quantitative and has a case control design. All menopausal mothers who experienced hypertension were 264 people (cases) and 196 people (controls). The sample was 64 people (simple random sampling). bivariate results of maternal age at menopause (0.00), heredity (0.00) and obesity (0.00). The variable most related to the incidence of hypertension is heredity. It is recommended that menopausal mothers pay more attention to the intake of salt, saturated fat and calories in their diet and prioritize regular physical activity as part of efforts to maintain heart health and reduce the risk of hypertension and it is recommended that the Sihapas Barumun Community Health Center can be used as eval_uation material for implementing a periodic screening program. to assess blood pressure, especially in menopausal women, and provide counseling about the importance of weight management and a healthy lifestyle.